Changes in stress and recovery during heavy training in male rowers - Jürimäe, J.; Mäestu, J.; Jürimäe, T. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Stressful high volume training periods are necessary to obtain high performance in sports. However, increase in performance is only achievable when athletes optimally balance training stress with adequate recovery [1,2]. The aim of this study was to investigate the stress and recovery perceived by highly trained male rowers and find possible relationships between perceived recovery-stress level, training load and selected blood biochemical parameters. Methods Twelve national level male rowers participated in this study. The study consisted of six weeks, where the first week was the reference week with a usual training volume. During the heavy training period (weeks 2, 3, 4), the training load was increased up to 40% and during recovery period (weeks 5, 6) training load was reduced by 15 % compared to the reference week. The Recovery-Stress Questionnaire for Athletes (RESTQ-Sport) [2] was used to assess the perceived recovery-stress state of rowers. Cortisol and creatine kinase values were obtained to assess blood biochemical response to heavy changes in training volume. Results RESTQ-Sport revealed that the recovery-stress state of rowers was significantly changed during heavy training and the following recovery periods. The changes were found in Emtional Stress, Social Stress, Fatigue, Somatic Complaints, Success, Somatic Relaxation, General Well-Being, Disturbed Breaks, Fitness/Injury, Being in Shape. Cortisol was not changed during the study period, but significant increases in creatine kinase activity were found during high training period (weeks 2, 3, 4) compared to reference period (week 1). Training load was significantly correlated to the Standardized RESTQ index (r=-0.39). The values of cortisol were significantly related to Standardized Stress score (r=0.76) and to Standardized RESTQ index (r= -0.59). The values of creatine kinase activity were significantly related to Standardized Recovery score (r=-0.45). Significant relationships were found between cortisol and General Stress, Emotional Stress, Social Stress, Conflicts/Pressure, Fatigue, Lack of Energy, Physical Complaints, General Well-Being, Sleep Quality, Emotional Exhaustion and Fitness/Injury (r>0.35).The values of creatine kinase activity were significantly related to Social Relaxation (r=-0.40), General Well-Being (r=-0.47) and Being in Shape (r=-0.35). Conclusions The results of present study demonstrated that using RESTQ-Sport, athletes and coaches can be informed of the importance of daily activities during heavy training period and specifically how these activities are related to the recovery-stress state in athletes. Using Standardized RESTQ index gives us a simplified picture of athletes´ current state.